Dr Oen Boen Ing; Patriot doctor, social activist, and doctor of the poor - Lie, Ravando (Wacana, Journal of the Humanities of Indonesia, 2017)
This article examines the efforts and achievements of Oen Boen Ing, a Tionghoa doctor, to improve the quality of health of the poorer inhabitants of Surakarta. Dr Oen played an important role in five different periods: Dutch colonialism, the Japanese occupation, the Indonesian revolution, Soekarno's regime, and Suharto's New Order. Known for being a benevolent doctor, activist, and patriot of the revolution during his life-time, Dr Oen also gave medical assistance to the needy, which famously earned him the accolade of "doctor of the poor". During the Indonesian revolution, Dr Oen assisted the Student Soldiers (Tentara Pelajar) and afterwards was appointed the member of Supreme Advisory Council (Dewan Pertimbangan Agung/DPA) by Soekarno in 1949. As a benevolent doctor and activist, Dr Oen is remembered for founding the Panti Kosala Hospital which was renamed to perpetuate his name on 30 October 1983, exactly a year after his passing. When he died, thousands of peoples gathered to pay their final respects to the doctor. He was honoured with a ceremony conducted in the Mangkunegaran Palace. Dr Oen's name will be eternally respected, especially in Surakarta.